LEADERSHIP IN ISLAMIC EDUCATION - Rizky Hanivan; Ahmad Balya Adiba (Journal of Higher Education and Academic Advancement, 2024)
This paper is a brief discussion of leadership in Islamic education management. Leadership is an activity in guiding a group so that the goals of the group are achieved, namely common goals. Leadership is an obligation if an organization wants to run effectively. Effective leadership indicates leadership delivered by a leader who is authoritative and wise in implementing his leadership strategy in order to realize the vision and mission that is held firmly by himself and his team and lead many people in a better direction. Because, leaders in organizations are managers who carry out management functions. A leader can carry out his role by providing assistance, namely by creating a good climate, the leader can also help the group in establishing work procedures. So this article aims to provide an overview of the role of leadership in improving the performance of educational institutions. Therefore, it is necessary to implement leadership functions in order to progress an organization. This paper was selected using the library research method by collecting various written sources to obtain conclusions from this research.